2011
DOI: 10.1039/c0ee00513d
|View full text |Cite
|
Sign up to set email alerts
|

Energy storage studies of bare and doped vanadium pentoxide, (V1.95M0.05)O5, M = Nb, Ta, for lithium ion batteries

Abstract: The bare V 2 O 5 and doped (V 1.95 M 0.05 )O 5 (M ¼ Nb, Ta) nano/submicron sized compounds were prepared by the simple polymer precursor method. The compounds were characterized by different physical and electroanalytical techniques. The effects of doping and different synthesis conditions on the energy storage performance of the V 2 O 5 compounds were discussed. All compounds delivered a discharge capacity (at the end of the 2 nd cycle) in the range 245 to 261 (AE3) mA h g À1 , except for the tantalum doped c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 63 publications
4
63
1
Order By: Relevance
“…The R ct values were found to increase in the fully discharged state (454 Ω) and decrease in the fully charged state (307 Ω). This indicates that the Li intercalation (discharge) was not as smooth as Li de-intercalation (charge) [39,40]. However, this structure provided much easier charge transfer at the electrode-electrolyte interface and consequently decreased the overall internal resistance of the cell, which accounts for the excellent rate capability and cycling stability of the electrode.…”
Section: Resultsmentioning
confidence: 98%
“…The R ct values were found to increase in the fully discharged state (454 Ω) and decrease in the fully charged state (307 Ω). This indicates that the Li intercalation (discharge) was not as smooth as Li de-intercalation (charge) [39,40]. However, this structure provided much easier charge transfer at the electrode-electrolyte interface and consequently decreased the overall internal resistance of the cell, which accounts for the excellent rate capability and cycling stability of the electrode.…”
Section: Resultsmentioning
confidence: 98%
“…44 Interestingly, formation of Mn 2 O 3 is understood from the appearance of new bands at 575 and 667 cm -1 , which could be attributed to the M-O bonds of Mn 2 O 3 (Fig. [47][48][49] Fig . 9,45 In order to get further information about the purity and chemical composition of the sample, we carried out X-ray photoelectron spectroscopy (XPS).…”
Section: Fig 1 Sem Images Of Hollow and Porous Mn 2 O 3 Microspheresmentioning
confidence: 99%
“…polyaniline and polypyrrole [5]). Among these materials, vanadium oxide [6][7][8][9][10] and metal-vanadium-based oxides [11][12][13][14] [15]. The electrochemical performance of FeVO 4 ·nH 2 O was also studied and it was found that the insertion capacity highly depends upon the water content [16][17][18].…”
Section: Introductionmentioning
confidence: 98%